ENHANCING CRITICAL HINKING SKILLS THROUGH AGILE PROJECT-BASED LEARNING IN VOCATIONAL EDUCATION (INTERNATIONAL SEMINAR, 2025)
This research explores the impact of integrating the Project-Based Agile Learning (PjBL–Agile) framework on the enhancement of vocational learners’ critical thinking competencies. The investigation was carried out in two state vocational institutions located in Pacitan Regency—SMK Negeri 1 Donorojo and SMK Negeri Pringkuku—with a total of 106 students majoring in Computer and Network Engineering. Participants were divided into experimental and control cohorts.The development of the instructional framework adopted the Research and Development. Data were gathered through pretest–posttest assessments, classroom observations, learner perception surveys, and reflective interviews.Findings revealed a consistent improvement in the experimental cohort’s critical thinking performance, with the mean score increasing from 24.31 to 32.14, while the control group showed only a marginal rise from 25.11 to 26.23. The N-Gain index of 0.499 indicated a moderate level of improvement for the experimental group, whereas the control group achieved a low-level gain of 0.076. Furthermore, results from the independent t-test confirmed a substantial difference between groups, t(138) = 10.96, p < 0.001.Qualitative evidence supported these numerical outcomes, demonstrating higher engagement, cooperation, and reflection among learners in the Agile-based setting. Collectively, the results highlight that the PjBL–Agile framework cultivates critical and adaptive thinking, while also strengthening collaborative and problem-solving abilities in 21st-century vocational contexts.